ICT innovation: A simple exchange system [farmet to farmer] - Puckett, Brian (Technical Centre for Agricultural and Rural Cooperation, 2012)
Next2's SMS service in Kenya and Nigeria lets farmers share local knowledge, expertise and experiences with each other, and with agricultural researchers